Preparation and Characterization of Polysulfone Membranes Reinforced with Cellulose Nanofibers - Reema H. Alasfar (14151717) (2022)
The mechanical properties of polymeric membranes are very important in water treatment applications. In this study, polysulfone (PSF) membranes with different loadings of cellulose nanofibers (CNFs) were prepared via the phase inversion method. CNF was characterized through transmission electron microscopy (TEM) and scanning electron microscopy (SEM). The pore morphology, mechanical properties, membrane performance and hydrophilicity of pure PSF membranes and PSF/CNF membranes were investigated. The changes in membrane pore structure with the addition of different CNF contents were observed using SEM images. It was shown that the calculated membrane pore sizes correlate with the membrane water fluxes. The pure water flux (PWF) of fabricated membranes increased with the addition of CNFs into the PSF matrix. It was shown that the optimal CNF loading of 0.3 wt.% CNF improved both the elastic modulus and yield stress of the PSF/CNF membranes by 34% and 32%, respectively (corresponds to values of 234.5 MPa and 5.03 MPa, respectively). This result indicates a strong interfacial interaction between the PSF matrix and the reinforced nanofibers. The calculated compaction factor (CF) showed that the membrane resistance to compaction could be improved with CNF reinforcement. Compared to pure PSF membrane, the hydrophilicity was significantly enhanced with the incorporation of 0.1 wt.%, 0.2 wt.% and 0.3 wt.% CNF, as shown by the water contact angle (WCA) results. It can be concluded that CNFs are homogeneously dispersed within the PSF matrix at CNF loading less than 0.5 wt.%. Other Information Published in: Polymers License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3390/polym14163317